Association Between Major Bleeding and In-Hospital Major Adverse Cardiovascular Events After Percutaneous Coronary Intervention in Acute Coronary Syndromes - Bekler, Özkan; Kurtul, Alparslan; Hancıoğlu, Emirhan; Kazan, Süleyman Diren; Şen, Fatih (Hämostaseologie, 2025)
Major bleeding (MB) is a serious complication in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary intervention (PCI). Although its association with long-term adverse outcomes is well documented, the impact of in-hospital MB on early cardiovascular prognosis remains incompletely characterized.To investigate the association between in-hospital MB and major adverse cardiovascular events (MACE) in patients with ACS treated with PCI.We conducted a retrospective cohort study on 829 consecutive ACS patients who underwent successful PCI between January 2021 and December 2023. MB was defined as Bleeding Academic Research Consortium (BARC) type 3 or 5 bleeding events. MACE was defined as a composite of all-cause mortality, recurrent myocardial infarction, ischemic stroke, urgent target vessel revascularization, or new-onset/decompensated heart failure with left ventricular ejection fraction (LVEF) <30%. Clinical data and outcomes were extracted from hospital records and independently adjudicated.MB occurred in 4.5% of patients (n = 37). The incidence of in-hospital MACE was significantly higher among patients with MB compared to those without (40.5% vs. 8.1%, p < 0.001). In multivariate logistic regression, MB was the strongest independent predictor of in-hospital MACE (OR: 12.43, 95% CI: 3.43–44.98, p < 0.001), followed by reduced LVEF (OR per % increase: 0.794, 95% CI: 0.747–0.843, p < 0.001), age, and white blood cell count.In-hospital MB is a potent and independent predictor of early MACE in patients with ACS undergoing PCI. These findings emphasize the need for careful risk stratification, bleeding prevention strategies, and individualized antithrombotic management in this high-risk population.
Keywords: acute coronary syndrome; percutaneous coronary ıntervention; major bleeding; major adverse cardiovascular events; dual antiplatelet therapy; BARC bleeding criteria; in-hospital outcomes